2020
DOI: 10.3390/ani10081316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Extruded Maize by Dried Citrus Pulp in a Mixed Diet on Ruminal Fermentation, Methane Production, and Microbial Populations in Rusitec Fermenters

Abstract: Citrus pulp is a highly abundant by-product of the citrus industry. The aim of this study was to assess the effects of replacing extruded maize (EM; 20% of total diet) by dried citrus pulp (DCP; 20%) in a mixed diet on rumen fermentation and microbial populations in Rusitec fermenters. The two diets contained 50% alfalfa hay and 50% concentrate, and the same protein level. Four Rusitec fermenters were used in a cross-over design with two 13-d incubation runs. After 7-d of diet adaptation, diet disappearance, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…These changes indicate that the biofermentation process significantly altered the chemical composition of the navel orange pulp. The high level of neutral detergent fiber content can be attributed to the rich content of hemicellulose, which may make the fiber in FNOP more easily fermentable in the gut [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…These changes indicate that the biofermentation process significantly altered the chemical composition of the navel orange pulp. The high level of neutral detergent fiber content can be attributed to the rich content of hemicellulose, which may make the fiber in FNOP more easily fermentable in the gut [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Methane production was reduced by 41.7% (mL), 41.6% (mL/g incubated DM), and 45.9% (mL/g degraded DM) in response to OEO1. García-Rodríguez et al ( 18 ) evaluated the effect of substituting extruded corn for dry citrus pulp (20%) and found that reductions in CH 4 were associated with the antimicrobial effects of bioactive compounds such as terpenoids, limonene, and citral. However, this was not observed for the OEO2 treatment, as there were no differences in CH 4 between OEO2 and the control.…”
Section: Discussionmentioning
confidence: 99%
“…Kotsampasi ( 11 ) reported that milk yield, milk fat yield, and feed efficiency of ewes were all enhanced when 450 mg/kg OEO (d-limonene, 95.17 g/100 g) was added to a ration with a 57:43 concentrate-to-forage ratio. The replacement of 20% extruded corn with citrus pulp containing bioactive compounds, such as limonene, reduced CH 4 production in dairy sheep ( 18 ). In tropical regions, forages are typically low in crude protein but high in neutral detergent fiber (NDF).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial (in vitro) rumen systems have been used for many years to make the ruminant industry more sustainable and to screen feed formulations and potential feed additives, such as ionophores, biologically active compounds sourced from plants, dietary lipids, and exogenous enzymes, for their impact on the rumen ecosystem and the host animal [11][12][13][14][15]. In vitro rumen models have been used extensively over several decades in the area of rumen microbiology and rumen nutrition, and whereas in early years, in vitro rumen models were used to only test changes in simple feed parameters, in recent years, the combination of more advanced in vitro systems with advanced omics and analytical approaches have made in vitro rumen systems very useful tools to enhance our understanding of rumen function and changes in rumen function in response to dietary changes at the molecular and the microbial level [16,17].…”
Section: Introductionmentioning
confidence: 99%